APPLICATION FOR SOLVING HOMOGENOUS ORDINARY DIFFERENTIAL EQUATIONS WITH CONSTANT COEFFICIENTS - Bakhtiyor Zokhirovich Usmonov (Web of Journals Publishing, 2024)
The article is dedicated to examples of the purposeful use of modern information technology tools, in particular, the use of mathematical packages, in order to increase the effectiveness of mathematics practical lessons.
Keywords: Information technologies, program, Maple, Desmos, Geogebra, graph, function.